CogniWin – A virtual assistance system for older adults at work - Hanke, S.; Meinedo, H.; Portugal, D.; Belk, M.; Quintas, J.; Christodoulou, E.; Sili, M.; Dias, J.; Samaras, G. (ITAP 2015: Human aspects of IT for the aged population: Design for everyday life, 2015)
This paper presents an innovative virtual assistant system, which aims to address older adults' needs in a professional environment by proposing promising and innovative virtual assistance mechanisms. The system, named CogniWin, is expected to alleviate eventual age related memory degradation and gradual decrease of other cognitive capabilities (i.e. speed of processing new information, concentration level) and at the same time assist older adults to increase their learning abilities through personalized learning assistance and well-being guidance. In this paper we describe the overall system concept, the technological approach, the methodology used in the elicitation of user needs, and describe the first pre-trials' evaluation.